2018
DOI: 10.1016/j.jvb.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent career success: The case of distinguished academics

Abstract: In a qualitative study, 28 distinguished academics (DAs) and eight of their spouses discussed career success in the boundaryless career contest. A boundaryless career is one that is based on independence rather than dependence on traditional organizational arrangements. The participants described career success in terms of why, how, and with whom. In describing the "why" of their work, the DAs were strongly driven in their research careers and explorations, believed that their academic field and research had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 74 publications
5
69
0
Order By: Relevance
“…This is particularly useful for those at the various intersections of identity such as gender, race, sexual orientation, or social class. Some examples of this include social class and upward mobility for White men (Kallschmidt & Eaton, 2018), intelligent career success for academics (Beigi, Shirmohammadi, & Arthur, 2018), and first-generation college students (Tate et al, 2015). There have been enough qualitative studies in specific areas to warrant reviews.…”
Section: View From 2019mentioning
confidence: 99%
“…This is particularly useful for those at the various intersections of identity such as gender, race, sexual orientation, or social class. Some examples of this include social class and upward mobility for White men (Kallschmidt & Eaton, 2018), intelligent career success for academics (Beigi, Shirmohammadi, & Arthur, 2018), and first-generation college students (Tate et al, 2015). There have been enough qualitative studies in specific areas to warrant reviews.…”
Section: View From 2019mentioning
confidence: 99%
“…The experiences of the respondents in London verify global cities as ‘transnational social spaces’ (Smith, 1999) or ‘transnational communities’ (Beigi et al, 2018) where knowledge is produced and disseminated globally through transnational networks. Miera (2008) exemplifies how Polish entrepreneurs in Berlin deploy their Polish skills and contacts to establish businesses aiming at the Polish community in Berlin and then successfully expand their enterprises back to Poland.…”
Section: Discussionmentioning
confidence: 98%
“…These arguments also add to the debate about the context-driven links between the three ways of knowing (Beigi et al, 2018;Parker et al, 2009), and therefore contribute to the intelligent career framework. The results provide further empirical evidence to illustrate how changes in one way of knowing entail changes in the others (Zikic and Ezzedeen, 2015).…”
Section: Confidence and Self-respect As Valuable Workers Lifestylementioning
confidence: 94%
See 1 more Smart Citation
“…These three different ways of knowing have been regarded as the critical aspects of career competency in the modern career environment (Suutari & Mäkelä, 2007). The previous studies showed that the three aforementioned career competencies are the critical predictors of many work performance aspects in various research settings (Beigi, Nayyeri, & Shirmohammadi, 2020;Beigi, Shirmohammadi, & Arthur, 2018;Colakoglu, 2011;Dickmann & Mills, 2010;Eby, Butts, & Lockwood, 2003;Suutari & Mäkelä, 2007;Zikic & Ezzedeen, 2015).…”
Section: Introductionmentioning
confidence: 99%